Pemeriksaan dan Pengobatan dalam Rangka Pemberantasan Pedikulosis Kapitis pada Anak Panti Asuhan: Indonesia - Maryanti, Esy; Lestari, Enny; Wirdayanto, Ade; Mislindawati, Mislindawati; Firja, Wira; Devlin, Muhammad (UII, 2024)
Pediculosis capitis is an infestation of head lice (Pediculus humanus capitis) with symptoms of itching on the head. Although it is not fatal, pediculosis capitis can interfere with daily activities, especially disrupting children's concentration and disrupting sleep quality. Head lice often affect school-aged children and people who have poor personal hygiene. An orphanage is a place where a group of children live together and is a place that is at risk of parasitic infections. This activity aims to carry out examinations for head lice to determine the incidence of pediculosis capitis, provide treatment to infested children and provide health education such as counseling and training to prevent in the context of eradicating pediculosis capitis in orphanages. This community service activity occurred at the Baiturrahmah Orphanage, Rimbo Panjang Village, Kampar Regency, Riau Province. The target audience is an orphanage, totaling 31 people, consisting of 14 (45.2%) girsl and 17 (54.8%) boys. At this activity, it was found that all the girls were infested with head lice and no boys were infected with Pediculus humanus capitis. Infected children are treated with 1% permethrin. In this activity, education was also provided to orphanage children and administrators about Pediculosis capitis including causes, clinical symptoms, treatment, prevention and eradication of infection. Each child is also given a serit comb, one child one serit comb. It is hoped that the treatment and education that has been provided can cure these diseases and improve the level of public health.